Case Report: Scalp pityriasis versicolor may be a neglected problem - Zhou, Ya Bin; Chao, Jin Jing; Ma, Lin; Xiao, Yuan Yuan (Frontiers in Pediatrics, 2024)
Pityriasis versicolor, a common skin fungal infection, is typically observed on trunk and limb skin. Here, we highlight an unusual presentation: scalp involvement, often overlooked due to its asymptomatic, mildly scaly patches. We report four pediatric cases, emphasizing the potential underestimation of this scalp variant. This case series underscores the importance of considering this diagnosis in patients with unexplained scalp hypopigmentation, especially in males with short hair who may readily notice these subtle changes. The report contributes to the understanding of this variant's clinical presentation and emphasizes the need for awareness among clinicians to ensure accurate diagnosis and appropriate management.